O púlpito barroco português e os seus conteúdos doutrinários e sociológicos : a pregação seiscentista do "Domingo das Verdades" - Marques, José (2004)
The sermon of the Portuguese Baroque is shaped by historical, cultural, sociological and devotional circumstances, marked by the milieu of the time and by Tridentine discipline and doctrinarian guidelines. Baroque preaching of an evangelical tone, when present, reverberated like a courageous denouncement of the lack of "fear of God and love of virtue". Occurrent pretexts were often used which led the sermon, perceptibly or subtly, down paths which revealed social and political concerns that needed to be addressed. The freedom enjoyed at the time by the pulpit is thus reflected in the orientation and contents which several canonical orators – like Father Antonio Vieira, Father Manuel da Silva, Friar Cristóvão de Almeida, Friar Cristóvão de Fóios and Friar Urbano de Santo António – bestowed on their sermons for the 5th Sunday of Lent, the Sunday of Reckoning ("Domingo das Verdades"). They are therefore some of the most emblematic specimens of the time, especially of the 1600s, by reason of the critical eye with which they viewed contemporaneous Portuguese society.